2014
DOI: 10.5194/amt-7-3989-2014
|View full text |Cite
|
Sign up to set email alerts
|

MISR research-aerosol-algorithm refinements for dark water retrievals

Abstract: Abstract. We explore systematically the cumulative effect of many assumptions made in the Multi-angle Imaging SpectroRadiometer (MISR) research aerosol retrieval algorithm with the aim of quantifying the main sources of uncertainty over ocean, and correcting them to the extent possible. A total of 1129 coincident, surface-based sun photometer spectral aerosol optical depth (AOD) measurements are used for validation. Based on comparisons between these data and our baseline case (similar to the MISR standard alg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 45 publications
0
92
0
Order By: Relevance
“…Recently, Kahn and Gaitley (2015) provided a thorough verification of MISR's aerosol type retrieval capabilities and Lee et al (2016) demonstrated that the MISR aerosol particle climatologies regionally showed good agreement with the results of chemical transport models. The current 74 mixture set, however, is not complete and has some documented deficiencies Kalashnikova et al, 2013;Limbacher and Kahn, 2014). A more comprehensive set of aerosol types and mixtures will be considered in a future release of the MISR's aerosol algorithm.…”
Section: Previous Misr V2dark Water Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kahn and Gaitley (2015) provided a thorough verification of MISR's aerosol type retrieval capabilities and Lee et al (2016) demonstrated that the MISR aerosol particle climatologies regionally showed good agreement with the results of chemical transport models. The current 74 mixture set, however, is not complete and has some documented deficiencies Kalashnikova et al, 2013;Limbacher and Kahn, 2014). A more comprehensive set of aerosol types and mixtures will be considered in a future release of the MISR's aerosol algorithm.…”
Section: Previous Misr V2dark Water Algorithmmentioning
confidence: 99%
“…The most frequently used metric that quantitatively characterizes the quality of a particular AOD dataset as a whole is the error envelope (EE) (Bréon et al, 2011;Garay et al, 2017;Kahn et al, 2010;Levy et al, 2010Levy et al, , 2013Limbacher and Kahn, 2014;Omar et al, 2013;Remer et al, 2008;Sayer et al, 2012Sayer et al, , 2013Witek et al, 2013). EE results from a validation study where a particular satellite AOD dataset is compared against another AOD dataset, typically ground-based information from the Aerosol Robotic Network (AERONET) (Dubovik et al, 2000;Holben et al, 1998), which is considered to represent the "truth".…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications, the uncertainties in whitecap estimates (fractional coverage and spectral reflectance, e.g., Frouin et al, 1996;Anguelova et al, 2006) need to be fully considered and incorporated into the analysis. The theoretical derivations used to estimate wind speed effects on surface reflectance for MODIS and MISR satellite aerosol retrievals explicitly include whitecaps and bubble rafts but not subsurface bubbles (Levy et al, 2013;Limbacher and Kahn, 2014). For future applications that require accurate estimations of atmospheric aerosol concentrations from satellite observations, oceanic bubble concentration is a factor that needs to be taken into consideration for ocean regions with strong near-surface winds.…”
Section: Discussionmentioning
confidence: 99%
“…Some Level 3 products (e.g., Zhang and Reid, 2008;Shi et al, 2011a) include an empirical correction for wind-speedrelated bias to retrieved AOD. Some Level 2 satellite retrievals (e.g., Sayer et al, 2010Sayer et al, , 2012Jackson et al, 2013;Levy et al, 2013;Limbacher and Kahn, 2014) also incorporate wind speed data into the radiative transfer calculations using parameterizations of wind effects on whitecaps and bubble rafts. The current study uses a unique combination of data sets to further investigate the mechanics of the ocean lower boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to Limbacher and Kahn (2014), the MISR RA simulated ocean surface was modeled as an isotropic (wind-speed-dependent only) Fresnel reflector (Cox-Munk), with whitecap reflectance included. In Limbacher and Kahn (2014), we made adjustments to the whitecap reflectance and added an ocean under-light term that includes molecular and particulate attenuation.…”
Section: Misr Ra Enhanced Ocean Reflectance Modelmentioning
confidence: 99%